Activation of aldehydes via oxidative n-heterocyclic carbene catalysis - Mo, Junming (2015)
My Ph.D research mainly focuses on developing new reactions and synthetic methods via oxidative N-Heterocyclic Carbene catalysis. This thesis contains four major parts: Chapter 1 gives a brief introduction to history and present development of NHC catalysis, and shows the challenges in NHC catalysis need to be overcome. Chapter 2 discloses the first example of enolate equivalents generated from cleavage of C-C bond promoted by NHC catalysts. The innovative cyclolization of enolate equivalents with chalcones is investigated. Chapter 3 describes the oxidative NHC-catalyzed direct β-activation of simple saturated aldehydes. The oxidation of enolate intermediate in NHC catalysis is realized at the first time. Chapter 4 introduces the γ-activation of β-methyl cinnamaldehyde mediated by NHC. Vinyl enolate intermediate generated from deprotonation of α,β-unsaturated acyl azolium reacts with activated ketone to offer δ-lactone. Challenging enantioselective control is realized by Lewis acid/NHC co-operative catalysis.